The Vat‐AIEC protease promotes crossing of the intestinal mucus layer by Crohn's disease‐associated Escherichia coli. (23rd November 2015) - Gibold, Lucie; Garenaux, Estelle; Dalmasso, Guillaume; Gallucci, Camille; Cia, David; Mottet‐Auselo, Benoit; Faïs, Tiphanie; Darfeuille‐Michaud, Arlette; Nguyen, Hang Thi Thu; Barnich, Nicolas; Bonnet, Richard; Delmas, Julien
Summary: The aetiology of Crohn's disease (CD) involves disorders in host genetic factors and intestinal microbiota. Adherent‐invasive Escherichia coli (AIEC) are receiving increased attention because in studies of mucosa‐associated microbiota, they are more prevalent in CD patients than in healthy subjects. AIEC are associated both with ileal and colonic disease phenotypes. In this study, we reported a protease called Vat‐AIEC from AIEC that favours the mucosa colonization. The deletion of the Vat‐AIEC‐encoding gene resulted in an adhesion‐impaired phenotype in vitro and affected the colonization of bacteria in contact with intestinal epithelial cells in a murine intestinal loop model, and also their gut colonization in vivo . Furthermore, unlike LF82Δ vat‐AIEC, wild‐type AIEC reference strain LF82 was able to penetrate a mucus column extensively and promoted the degradation of mucins and a decrease in mucus viscosity. Vat‐AIEC transcription was stimulated by several chemical conditions found in the ileum environment. Finally, the screening of E .  coli strains isolated from CD patients revealed a preferential vat‐AIEC association with AIEC strains belonging to the B2 phylogroup. Overall, this study revealed a new component of AIEC virulence that might favour their implantation in the gut of CD patients. Abstract : The adherent‐invasive Escherichia coli (AIEC) prevalent in the intestinal mucosa of Crohn's disease (CD) patients are able to overcome the protective mucus layer to interact with intestinal cells. We demonstrated that AIEC produce a protease, VAT‐AIEC, which cleaves mucins and promotes mucus penetration of AIEC strains, enhancing adhesion to epithelial cells. VAT‐AIEC contributes to AIEC gut colonization in murine model. Our results strongly suggest that this protease might be involved in AIEC gut colonization favoring chronic inflammation in CD patients.